Avaliação in vitro da interferência do herbicida glyphosate no controle endócrino do crescimento ovariano por neuro-hormônios e prostaglandinas, no caranguejo do estuário Neohelice granulata - Canosa, Ivana Sofía (2022)
Adult females of the crab Neohelice granulata sampled at from Samborombón Bay (Buenos Aires Province, Argentina), were used. Several in vitro tests were carried out during the pre-reproductive period, in order to evaluate the growth of the isolated ovary in the presence of the herbicide (in its commercial formulation Roundup) and/or extracts of neuroendocrine organs or inhibitors of prostaglandin synthesis. For each assay, 12 females were used, assigning a different treatment to each portion of the ovary of the same female (randomized block design). The ovary pieces were incubated for 24 h in M199 culture medium, at 24 ºC and controlled atmosphere. At the end of each assay, the ovaries were processed either for histological analysis or to determine the levels of vitellogenin (Vg) using the ELISA technique. The results of the assays conducted with extracts of eyestalk or thoracic ganglion indicated that Roundup (RUP) addition did not significantly (p>0.05) modify the effect of such extracts on ovarian growth. However, in order to assess whether the effect of RUP on isolated ovaries is related to the hormonal signaling exerted by prostaglandins (PG), an in vitro assay with ibuprofen (IBF, inhibitor of PG synthesis) was performed. The level of Vg in the treatment with RUP 0.2 mg/L + IBF 10 mg/L was significantly lower (p<0.05) than that of the Control, RUP 0.2 mg/L, or IBF 10 mg groups. Although RUP per se produced a decrease (p<0.05) in Vg levels, compared to control, its combination with IBF caused a higher (p<0.05) decrease. Given the additivity of inhibitory effects observed between ibuprofen and the RUP, it is plausible to propose that the mode of action of the RUP could be due to the inhibition of the endogenous synthesis of PGs in the ovary, although the possible interference of the RUP with the PGs receptor, or the inhibition of some step in the prostaglandin hormone transduction pathway, cannot yet be ruled out.